SCIENTIFIC AND THEORETICAL FUNDAMENTALS FORMATION OF CREATIVE THINKING DESIGNERS - A.A. Marchenko (Academy of Cognitive and Natural Sciences, 2022)
In this article is studied question about creative abilities in common and creating creative views in the way of parts.